2010
DOI: 10.4049/jimmunol.0804106
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin-Activated Plasmacytoid Dendritic Cells Induce the Generation of FOXP3+ Regulatory T Cells in Human Thymus

Abstract: Human thymus contains major dendritic cell (DC) subsets, myeloid DCs (mDCs), and plasmacytoid DCs (pDCs). We previously showed that mDCs, educated by thymic stromal lymphopoietin (TSLP) produced by the epithelial cells of the Hassall’s corpuscles, induced differentiation of CD4+CD25− thymocytes into Forkhead Box P3+ (FOXP3+) regulatory T cells (TR) within the medulla of human thymus. In this study, we show that pDCs expressed the TSLP receptor and IL-7 receptor a complexes upon activation and became responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(145 citation statements)
references
References 43 publications
6
136
0
3
Order By: Relevance
“…The observation that synthesis of TGF-b was enhanced in pancreatic Tregs recruited by CCL22-producing splenic CD8a 2 mDCs, although IL-10 was not detected (Fig. 3D), is in accordance with the report that human CD8a 2 mDCs are able to synthesize CCL22 upon activation with thymic stromal lymphopoietin, promoting the accumulation of TGF-b + rather than IL-10 + Tregs (17). CCL22 attracts CCR4-expressing T cells that include activated memory T cells and Tregs, the latter expressing high levels of the chemokine receptor CCR4 (15).…”
Section: Cd8asupporting
confidence: 79%
“…The observation that synthesis of TGF-b was enhanced in pancreatic Tregs recruited by CCL22-producing splenic CD8a 2 mDCs, although IL-10 was not detected (Fig. 3D), is in accordance with the report that human CD8a 2 mDCs are able to synthesize CCL22 upon activation with thymic stromal lymphopoietin, promoting the accumulation of TGF-b + rather than IL-10 + Tregs (17). CCL22 attracts CCR4-expressing T cells that include activated memory T cells and Tregs, the latter expressing high levels of the chemokine receptor CCR4 (15).…”
Section: Cd8asupporting
confidence: 79%
“…In agreement, it was recently suggested that human Treg-cell progenitors may selectively reside within mature DP thymocytes expressing high levels of CD69 and TCR-ab, since these cells develop into CD4SP Treg cells in response to activated autologous plasmacytoid and myeloid DCs [40], although not excluding the possibility of FOXP3 induction at the SP stages [41,42]. Additionally, our multiple regression analyses show a significant statistical dependency of the FOXP3 1 DP and SP populations, further supporting their direct precursor-product association.…”
Section: Discussionmentioning
confidence: 79%
“…This further supported the role of pDC such as a cellular source of TGF-b, like TGF-b-producing Tregs (32,34), to polarize Th17 cells. In contrast, human thymic pDC have been involved in Treg induction when stimulated by the thymic stromal lymphopoietin produced by the thymic epithelial cells (39). Therefore, depending on the microenvironment, pDC might be a key player in TGF-b-dependent T cell commitment such as Tregs and Th17 cells.…”
Section: Discussionmentioning
confidence: 92%